Analysis of Sharia Compliance and Accountability in the Distribution of Zakat Fitrah: A Case Study in the Village of Uman Agung - Ari Fatihatul Hidayah; Wulan Purnama Sari (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: This study examines the practice of zakat fitrah distribution in Uman Agung Village at Nur Hidayah Mosque, with a particular focus on its conformity with Islamic sharia principles and accountability. Methodology: Employing a descriptive qualitative approach, data were collected through field observations and a review of relevant literature on zakat fitrah. Findings: The findings reveal inaccuracies in the distribution process, whereby several recipients did not meet the criteria of mustahik as stipulated in Surah At-Tawbah verse 60, including widows and residents who are economically capable. These findings are analyzed using Sharia Compliance Theory and Islamic Accountability Theory, both of which emphasize the importance of accurate targeting, transparency, and responsibility in zakat management. This study underscores the necessity of providing education to zakat administrators and implementing a more rigorous verification system to ensure that zakat is distributed appropriately and in accordance with Islamic sharia principles.